Exciting opportunity for primary care dental practitioners - Hamilton, Alice R; Ricketts, David; Colloc, Thibault; Clarkson, Jan E (British dental journal, 2023)
Key pointsHighlights the past lack of research taking place in primary care dentistry and the importance of it in the future.Highlights two ongoing large pragmatic clinical trials taking place in primary care, investigating minimally invasive dental techniques versus conventional treatment options.Provides an opportunity for general dental practitioners to participate in high-impact research.